تعليم اللغة العربية في مدرسة البصيرة الدولية بماليزيا: عقبات وحلول = Teaching the Arabic language at Al-Basira International School in Malaysia: obstacles and solutions - Jasim, Alaa Khudair (IIUM Press, 2024)
تهدف هذه الدراسة إلى معرفة أبرز المعوقات التي تواجه تدريس اللغة العربية لغير الناطقين بها والحلول المقترحة لها، سواء كانت على مستوى المتعلم (الطالب)، أو المنهج المقرر، أو البيئة اللغوية؛ سعيًا في تطوير واقع تعليم اللغة العربية في مدرسة البصيرة وكذلك المدارس التي تشترك في نفس الأهداف والرؤى. وقد تحددت الدراسة بمحددات مكانية تعود إلى بيئة مدرسة البصيرة الدولية، وكذلك موضوعية تتعلق بتعليم اللغة العربية لغير الناطقين بها. وقد استندت الدراسة إلى مجموعة من المقابلات والمناقشات مع معلمي المدرسة من ذوي الاختصاص والخبرة في تدريس اللغة العربية، إضافة إلى متابعة مخرجات العملية التعليمية من خلال الإدارة. وأخيرا فقد خلصت الدراسة إلى أن العقبات التي تواجه تدريس اللغة العربية كثيرة ومتنوعة، فمنها ما يتعلق بالمتعلمين (الطلاب)، فقد تتنوع لغاتهم وثقافاتهم ودوافعهم اتجاه تعلم اللغة العربية، وبالتالي إضفاء نوع من التعقيد اتجاه عملية التعليم، كذلك فمن العقبات ما يرجع إلى المنهج المقرر، الذي يفتقر - في كثير من أنواعه - إلى المحتوى المناسب في محتواه اللغوي، ووسيلته التي تراعي الأبعاد الثقافية والنفسية للمتعلم، وأما العقبة الأخيرة فتتعلق بالبيئة اللغوية (الرسمية وغير الرسمية)، حيث تفتقر - في كثير منها - إلى العناصر اللازمة لتحقيق أغراض الاتصال اللغوي. ***** This study aims to identify the most prominent obstacles facing teaching the Arabic language to non-native speakers and the proposed solutions to them, whether at the level of the learner (student), the prescribed curriculum, or the linguistic environment. To develop the reality of teaching the Arabic language at Al-Basira School as well as schools that share the same goals and visions. The study was determined by spatial determinants dating back to the environment of Al-Basira International School, as well as objective parameters related to teaching the Arabic language to non-native speakers. The study was based on a set of interviews and discussions with schoolteachers with expertise and experience in teaching the Arabic language, in addition to following up on the outcomes of the educational process through the administration. Finally, the study concluded that the obstacles facing teaching the Arabic language are many and varied. Some of them are related to the learners (students), as their languages, cultures, and motivations towards learning the Arabic language may vary, thus adding a kind of complexity to the teaching process. Likewise, some of the obstacles are related to the prescribed curriculum. , which lacks - in many of its types - the appropriate content in its linguistic content, and its method that takes into account the cultural and psychological dimensions of the learner, and the last obstacle is related to the linguistic environment (formal and informal), as it lacks - in many of them - the necessary elements to achieve the purposes of linguistic communication. .